Rapid and precise diagnosis of pneumonia coinfected by Pneumocystis jirovecii and Aspergillus fumigatus assisted by next-generation sequencing in a patient with systemic lupus erythematosus: a case report - Yili Chen; Lu Ai; Yingqun Zhou; Yating Zhao; Jianyu Huang; Wen Tang; Yujian Liang (BMC, 2021)
Abstract Background Pneumocystis jirovecii and Aspergillus fumigatus, are opportunistic pathogenic fungus that has a major impact on mortality in patients with systemic lupus erythematosus. With the potential to invade multiple organs, early and accurate diagnosis is essential to the survival of SLE patients, establishing an early diagnosis of the infection, especially coinfection by Pneumocystis jirovecii and Aspergillus fumigatus, still remains a great challenge. Case presentation In this case, we reported that the application of next -generation sequencing in diagnosing Pneumocystis jirovecii and Aspergillus fumigatus coinfection in a Chinese girl with systemic lupus erythematosus (SLE). Voriconazole was used to treat pulmonary aspergillosis, besides sulfamethoxazole and trimethoprim (SMZ-TMP), and caspofungin acetate to treat Pneumocystis jirovecii infection for 6 days. On Day 10 of admission, her chest radiograph displayed obvious absorption of bilateral lung inflammation though the circumstance of repeated fever had not improved. Unfortunately, the patient discharged from the hospital since the financial burden, and during the follow-up, it was documented the patient died within one week after discharge. Conclusions This successful application of the next generation sequencing assisting the rapid diagnosis of Pneumocystis jirovecii and Aspergillus fumigatus coinfection provides a new perspective in the clinical approach against the systematic fungi infections and highlights the potential of this technique in rapid etiological diagnosis.